Answer:
(a) The value of
is (z+1)(3-z).
(b) The next term in the sequence is -2.
Step-by-step explanation:
(a)
It is given that arithmetic sequence that starts with an initial index of 0.
The initial term is 3 and the common difference is -2.
![a_0=3](https://tex.z-dn.net/?f=a_0%3D3)
![d=-2](https://tex.z-dn.net/?f=d%3D-2)
We need to find the value of
.
![s_z=\sum_{n=0}^{n=z}(a+nd)](https://tex.z-dn.net/?f=s_z%3D%5Csum_%7Bn%3D0%7D%5E%7Bn%3Dz%7D%28a%2Bnd%29)
where, a is initial term and d is common difference.
![s_z=\sum_{n=0}^{n=z}(3-2n)](https://tex.z-dn.net/?f=s_z%3D%5Csum_%7Bn%3D0%7D%5E%7Bn%3Dz%7D%283-2n%29)
The sum of an arithmetic sequence with initial index 0 is
![s_n=\frac{n+1}{2}[2a+nd]](https://tex.z-dn.net/?f=s_n%3D%5Cfrac%7Bn%2B1%7D%7B2%7D%5B2a%2Bnd%5D)
where, a is initial term and d is common difference.
Substitute n=z, a=3 and d=-2 in the above formula.
![s_z=\frac{z+1}{2}[2(3)+z(-2)]](https://tex.z-dn.net/?f=s_z%3D%5Cfrac%7Bz%2B1%7D%7B2%7D%5B2%283%29%2Bz%28-2%29%5D)
![s_z=\frac{z+1}{2}[2(3-z)]](https://tex.z-dn.net/?f=s_z%3D%5Cfrac%7Bz%2B1%7D%7B2%7D%5B2%283-z%29%5D)
![s_z=(z+1)(3-z)](https://tex.z-dn.net/?f=s_z%3D%28z%2B1%29%283-z%29)
Therefore the value of
is (z+1)(3-z).
(b)
The given arithmetic sequence is
7, 4, 1, ...
We need to find the term in the sequence.
In the given arithmetic sequence the first term is
![a=7](https://tex.z-dn.net/?f=a%3D7)
The common difference of the sequence is
![d=a_2-a_1\Rightarrow 4-7=-3](https://tex.z-dn.net/?f=d%3Da_2-a_1%5CRightarrow%204-7%3D-3)
The first term is 7 and common difference is -3.
Add common difference in last given term, i.e., 1, to find the next term of the sequence.
![1+(-3)=1-3=-2](https://tex.z-dn.net/?f=1%2B%28-3%29%3D1-3%3D-2)
Therefore the next term in the sequence is -2.